CORN RHIZOBACTERIA AS PROMISING BIOINOCULANTS FOR INCREASING PLANT PRODUCTIVITY AND PROTECTION (Eurasian Journal of Ecology, 2025)
Agricultural production is increasingly challenged by soil degradation, nutrient imbalance, and the prevalence of plant pathogenic fungi, which collectively threaten crop productivity and ecological stability. As a sustainable alternative to chemical inputs, plant growth-promoting rhizobacteria (PGPR) have gained considerable attention due to their ability to enhance plant vigor through natural biochemical mechanisms. This study focused on isolating and characterizing autochthonous bacterial strains associated with the rhizosphere of the maize hybrid KazZP 200 (Zea mays L.) and evaluating their functional traits relevant to plant growth promotion and biological control.A total of 25 bacterial isolates were obtained, comprising 15 Gram-negative and 10 Gram-positive strains. Based on a comparative screening of beneficial traits, two isolates - BJ14 and BJ18 - were selected for detailed investigation. Their functional potential was assessed through several key indicators, including the production of indole-3-acetic acid (ИСҚ), solubilization of insoluble phosphorus, biological nitrogen fixation, and antifungal activity against major phytopathogens. Among the tested isolates, BJ18 produced the highest level of ИСҚ (61.4 mg/mL) and demonstrated superior phosphate-solubilizing activity, suggesting a strong capability to stimulate root development. Isolate BJ14 showed the highest inhibitory effect against both phytopathogens, inhibiting the growth of Pythium spp. by 73% and the development of Alternaria alternata by 62–63%, and was distinguished by its stable and pronounced biocontrol activity. The results clearly indicate that these maize-associated rhizobacteria possess multifunctional traits that may significantly contribute to improving nutrient acquisition, promoting plant growth, and mitigating pathogenic stress. Such characteristics highlight their value as potential bioinoculants for sustainable crop production systems. The findings emphasize the importance of integrating locally adapted PGPR strains into eco-friendly agricultural technologies aimed at reducing chemical fertilizer dependency and enhancing soil health.Key words: rhizobacteria, PGPR, ИСҚ, phosphate solubilization, zinc solubilization, antifungal activity